2013
DOI: 10.1021/jp403929r
|View full text |Cite
|
Sign up to set email alerts
|

Structural Modelling of Silicon Carbide-Derived Nanoporous Carbon by Hybrid Reverse Monte Carlo Simulation

Abstract: An atomistic model of the nanoparticle size Silicon Carbide Derived Carbon (SiC-CDC) is constructed using the Hybrid Reverse Monte Carlo (HRMC) simulation technique through a two-step modeling procedure. Pore volume and three-membered ring constraints are utilized in addition to the commonly used structure factor and energy constraints in the HRMC modeling to overcome the challenges arising from uncertainties involved in determining the structure. The final model is characterized for its important structural f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
120
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(129 citation statements)
references
References 50 publications
9
120
0
Order By: Relevance
“…Nevertheless, despite moderate success, this method is unable to satisfactorily capture topological and morphological characteristics of the experimental sample. In contrast, it is well-demonstrated that realistic modeling of disordered porous materials is better achieved using the Hybrid Reverse Monte Carlo modeling (HRMC) technique, so that the final constructed model can reproduce many characteristic properties of the experimental sample including structural features, equilibrium gas adsorption and transport properties of the fluid in the target material [18,[25][26][27][28][29].…”
Section: ୀଵmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, despite moderate success, this method is unable to satisfactorily capture topological and morphological characteristics of the experimental sample. In contrast, it is well-demonstrated that realistic modeling of disordered porous materials is better achieved using the Hybrid Reverse Monte Carlo modeling (HRMC) technique, so that the final constructed model can reproduce many characteristic properties of the experimental sample including structural features, equilibrium gas adsorption and transport properties of the fluid in the target material [18,[25][26][27][28][29].…”
Section: ୀଵmentioning
confidence: 99%
“…This constraint controls the pore volume of the model by mimicking the experimental porosity of the target experimental sample through grid occupancy of the simulation cell, with associated error [27,31] …”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from the abundance of inter-layer boundaries due to their nanoscale size, intra-layer defects have also been observed in recent atomic-resolution electron microscopy studies [12][13][14], including in the form of non-hexagonal rings. Structural models, that captures microporosity as well as defective carbonaceous skeleton have been proposed of this material [1,9,10,12,15,16] although there is still debate over their validity [1]. A quantitative understanding of this defective structure is important for tailoring NPCs to have desired characteristics in the contexts of adsorption [14], thermal [17] and electrical [18] conductivity, and…”
Section: Introductionmentioning
confidence: 99%